What the Monk’s Habit Hides: Excavating the Silent Truths in Marguerite de Navarre’s Heptaméron 31 - Zegura, Elizabeth Chesney (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2015)
In Heptaméron 31, Marguerite de Navarre portrays a lascivious “Cordelier” or Franciscan who takes over a matron’s household during her husband’s absence, kills her servants, and disguises the woman as a monk before abducting her. Despite its surface resemblance to Rutebeuf’s “Frère Denise,” which also unveils a Franciscan’s lechery, Marguerite’s narrative is not a simple anticlerical satire. Within it we find a critique of the over-trusting husband, metaphors of censorship, an inquest into the dialectics of silence and (in)sight, a foregrounding of the victims’ body language, and analogies between the body politic and the body of the family. With these tools Marguerite folds into her nouvelle an allegory of reading; a cautionary tale about the dangers of mistaking outward “works” for true godliness; and an histoire tragique with political overtones that figure a crisis of authority between Reform theology’s “two kingdoms,” or secular and sacred governance, in sixteenth-century France.